2020
DOI: 10.1177/0036850420930971
|View full text |Cite
|
Sign up to set email alerts
|

Application of an innovative ridge-ladder-shaped polycrystalline diamond compact cutter to reduce vibration and improve drilling speed

Abstract: Polycrystalline diamond compact bits have been widely used in the Oil and Gas drilling industry, despite the fact that they may introduce undesired vibration into the drilling process, for example, stick-slip and bit bounce, which accelerate the failure rate and lead to higher drilling costs. First, we develop an innovative ridge-ladder-shaped polycrystalline diamond compact cutter, which has ridge-shaped cutting faces and multiple cutting edges with stepped distribution, in the hope of reducing vibration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…After ensuring the steady-state temperature of the bit, the temperature of the PDC bit cutting teeth at any distance from the interface at any time can be expressed as: 36 where p is the distance to the PDC bit cutting teeth, t is the cutting time, ρ2 is the density of cutting teeth, and T0normal″ is the environmental temperature.…”
Section: Temperature Model Of Pdc Bit Cutting Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…After ensuring the steady-state temperature of the bit, the temperature of the PDC bit cutting teeth at any distance from the interface at any time can be expressed as: 36 where p is the distance to the PDC bit cutting teeth, t is the cutting time, ρ2 is the density of cutting teeth, and T0normal″ is the environmental temperature.…”
Section: Temperature Model Of Pdc Bit Cutting Teethmentioning
confidence: 99%
“…Polycrystalline diamond compact (PDC) is a special super-hard material synthesized by artificial diamond and cemented carbide in one-time synthesis under high-temperature conditions, 1 which not only has the advantages of high hardness and wear resistance of diamond, but also has the characteristics of strong impact resistance and large blade emergence. Using it as the bit cutting teeth can improve the drilling efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the PCD can be widely used in the processing field of non-ferrous metals alloys, ceramics, difficult-to-machine composite materials, etc. [1][2][3][4]. In the sintering process of PCD under high pressure, Co is often used as the metal binder [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Their indoor experimental findings indicated that, in comparison to axe and conventional cutters, the spine-step cutter manifested a reduction in lateral force, longitudinal force, and overall cutting force during the rock-fracturing process. Utilizing numerical simulations, a comprehensive drilling process comparison was executed among these cutter designs, which unveiled that the spine-step tooth configuration effectively precludes stick-slip vibrations in drilling operations while simultaneously enhancing rock-fracturing efficiency [12]. Yang et al engineered a hard alloy drill bit with a non-smooth surface, drawing inspiration from the drag reduction and wear-resistant properties evident in beetle surfaces.…”
Section: Introductionmentioning
confidence: 99%